BOOK REVIEW: RUTH HEHOLT, MELISSA EDMUNDSON, "GOTHIC ANIMALS: UNCANNY OTHERNESS AND THE ANIMAL WITH-OUT", LONDON: PALGRAVE MACMILLAN, 2020, 307 P. - Ana-Maria SPÂNU (Studia Universitatis Babeş-Bolyai. Philologia, 2022)
This Palgrave collection of studies on animals and literature, edited by Ruth Heholt and Melissa Edmundson, brings together a series of cross-disciplinary approaches meant to reconceptualize the relationship between human and non-human literary beings in such a way as to acknowledge the continuum of sentience and affect between them. Ranging from of an analysis of faux documentaries about spectral predators to a diachronic incursion into the universe of American superhero comics, the studies are both rigorous and captivating. The collection as a whole revolves around the “animal turn” in historical, anthropological, philosophical and literary research and on this new momentum within the field of English studies, as I will try to show with reference to a few of the texts included here.